PENGARUH PEMBEBASAN LAHAN TERHADAP RISIKO PROYEK KONSTRUKSI (STUDI KASUS SOCIAL ENGINEERING PROYEK JALAN TOL RUAS SEMARANG BAWEN) - Ferry Hermawan; Frida Kistiani; Tanto Djoko Santoso (TEKNIK, 2011)
Semarang-Solo toll road has strategic significance for the development of the national road network inparticular in Central Java and also for the development of road networks in the regional scale. At stage 1 is thesegment Semarang-Bawen along 23.1 km is divided into sections 1 Semarang-Ungaran along 14.1 km requireland acquisition area of 52.23 Ha and 7.8 km long in Semarang district with an area of land acquisition needs60.37 Ha. Although he was pursued through the vacant lands, but in reality also crossed the road infrastructureor splitting the existing environment. Land acquisition is a fundamental problem of construction project and it ispart of the risk of infrastructure procurement. Purely technical approach sometimes can not always solve theproblem to minimize the risk. So this condition is sometimes often be in the realm of social engineering.